Effects of insufficient air injection on methanogenic Archaea in landfill bioreactor - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (ELSEVIER, 2007)
In this study, methanogenic Archaea diversity in an aerated landfill bioreactor filled with co-disposed incineration bottom ashes and shredded incombustible wastes was monitored and analyzed as a function of time using molecular techniques. Besides, the effects of insufficient air injection on the bioreactor performance and methanogenic diversity were evaluated thoroughly. Results indicated that rapid bio-stabilization of solid waste are possible with aerated landfill bioreactor at various oxygen and oxidation reduction potential levels. Slot-blot hybridization results of leachate samples collected from aerated landfill bioreactor showed that archaeal and bacterial activities increased as stabilization accelerated and bacterial populations constituted almost 95% of all microorganisms. The results of slot-blot hybridization and phylogenetic analysis based on 16S rRNA gene revealed that Methanobacteriales and Methanomicrobiales were dominant species at the beginning while substituted by Methanosarcina-related methanogens close to the end of the operation of bioreactor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: landfill; aeration; incineration ash; methanogen; molecular methods; 16S RIBOSOMAL-RNA; COMMUNITY STRUCTURE; LEACHATE; DIVERSITY; GENE; QUANTIFICATION; POPULATIONS; PROBES; SOIL